Ruminal effects of Rumensin during cold stress - Robinson, J.B.; Ames, D.R.; Nichols, David A. (Kansas State University. Agricultural Experiment Station, 2011)
Two trials were conducted to determine the effects of Rumensin in cold-stressed cattle. Steers fed diets with and without Rumensin were exposed to cold stress (0 C) and thermoneutrality (20 C). Rumen volatile fatty acids and rumen vault gases were sampled to monitor rumen fermentation. Although not statistically significant, Rumensin decreased rumen acetate to propionate ratios and increased CO2/CH4 ratios in both thermal environments. Such a methane decease should improve feed efficiency because less energy is wasted. Thus, Rumensin appears to support a more efficient rumen fermentation in cold stress as well as thermoneutrality.
Keywords: Beef; Rumen; Cold stress; Thermoneutrality; Fermentation